Characteristics and outcomes of children, adolescents and young adults with relapsed/refractory non-hodgkin lymphoma undergoing autologous stem cell transplant - Oren Pasvolsky; Roland L. Bassett; Sassine Ghanem; Branko Cuglievan; Priti Tewari; Chitra Hosing; Samer Srour; Jeremy Ramdial; Kris M. Mahadeo; Sajad Khazal; Demetrios Petropoulos; Uday Popat; et al. (BMC Cancer, 2023)
Abstract Background There is paucity of data regarding outcomes of children, adolescents and young adults (CAYA) patients with non-Hodgkin lymphoma (NHL) undergoing autologous stem cell transplantation (ASCT). Methods Patients aged 0–39 years undergoing first ASCT for NHL at MD Anderson Cancer Center between 2000 and 2020 were analyzed. Results Two hundred twenty-one patients were included in the analysis, 129 (58%) were male and the median age was 32 (range 6–39) years. The most common histological subtypes were diffuse large B cell lymphoma (DLBCL) (44%), T-NHL (19%) and primary mediastinal B-Cell lymphoma (PMBCL) (19%). Younger patients (age ≤ 25) had lower incidence of DLBCL and higher incidence of PMBCL and T-NHL compared to older patients (age > 25) (P = 0.02). None of the younger patients had double hit (DH)/double expressor (DE) DLBCL, compared to 14 patients in the older age group (18%, P = 0.07). Considering the three main aggressive NHL subtypes (DLBCL, PMBCL and T-NHL), younger patients had numerically better 15-year post-transplant progression free survival (PFS) (67% vs. 54%) and overall survival (OS) (71% vs. 62%) compared to older patients, yet these differences did not reach statistical significance (P = 0.19 and P = 0.24, respectively). In multivariate analysis, not achieving a CR prior to ASCT was independently predictive of worse PFS [partial remission (PR) (HR, 3.9); stable disease (SD) (HR, 18.0), P = 0.03] and of worse OS [PR (HR, 4.2), SD (HR, 6.5) and progressive disease (HR, 4.7), P < 0.0001]. DH/DE status was an independent adverse predictor of PFS in multivariate analysis (HR 5.8, p = 0.03). Ten patients (4.5%) (all aged > 25 years) developed second primary malignancies (SPM), at a median of 34.4 (range, 1.0–196.6) months after ASCT, and SPM was the cause of death in five (50%) of them. Conclusions CAYA NHL patients aged ≤ 25 years who received ASCT presented a distinct NHL histology as compared to older CAYA patients, and none in this younger age group had DH/DE DLBCL. We observed a trend towards improved PFS and OS in younger patients. Disease status at ASCT was predictive of both PFS and OS. DH/DE status was an adverse predictor of PFS.